Evaluation of Consumer Satisfaction with Microwave Burger Purchases at Lawson Surabaya in Support of SDGs 12 - Beatrice Maria Charmenita Napitupulu; Sri Widayanti; Prasmita Dian Wijayati (Universitas Muhammadiyah Palembang, 2026)
Changes in urban lifestyles characterized by high mobility and limited time have led to an increase in demand for practical and easily accessible fast food. One popular product is the microwave burger sold at Lawson. The increase in consumption of processed fast food not only affects consumer behavior but is also closely related to the principles of responsible consumption and production as outlined in Sustainable Development Goals (SDGs) 12. This study aims to evaluate customer satisfaction with purchasing microwave burgers at Lawson Surabaya in terms of price, product, ease of obtaining, packaging, packaging design, service and analyze its contribution to the implementation of SDGs 12. A descriptive quantitative approach was used for this study, with 97 respondents selected through sampling using accidental sampling techniques with the characteristics of respondents who have consumed burgers and are above 17 years old. Data analysis was carried out using the Customer satisfaction Index (CSI) after conducting validity and reliability tests. The results showed a CSI value of 83.984%, which is included in the